Validating and Testing Learning Transfer System Inventory (LTSI) in a Developing Country Context: A Case of Pakistan’s Service Sector - ZEESHAN HUSSAIN; MUHAMMAD NAUMAN HABIB; ZUNNOORAIN KHAN; SAQIB SHAHZAD (Journal of Business & Tourism, 2021)
Learning Transfer System Inventory (LTSI) is a tool used to measure the impact of various factors on learning outcomes. The objective of the study was to understand the problems faced by Pakistan service sector employees and finally to evaluate the impact of motivation scale, environment scale and trainee ability scale on outcome scale.Questionnaire of Learning Transfer System Inventory adopted from Holton, Bates and Ruona (2000) was used.569 questionnaires were administered to the employees of Peshawar service sector including employees of banks, non-government organizations, education and health sectors, out of which 415 were completed with a response rate of 73%.Correlation analysis shows that value of R is 0.969 that means there is 96.9% correlation in variables that are considered in model. The value of R Square is 0.939. In Service Sector, Supervisor Sanction Variable, Performance Outcome Expectation Variable and Performance Coaching Variable are insignificant and do not bring change in our dependent variable Outcome. Standardized Coefficients show that Personal Capacity for Transfer Variable, Peer Support Variable, Supervisor Support Variable and Transfer Effort Performance Expectation Variable having higher Standardized Coefficients betas, that means those variables bring greater change in dependent variable Outcome.